ИННОВАЦИОН ҒОЯЛАРНИ ИШЛАБ ЧИҚИШДА ИЛМИЙ ТАДҚИҚОТ МЕТОДЛАРНИНГ АҲАМИЯТИ - Турдимамбетов, И.Р.; Никадамбаева, Х.Б. (SCIENCE and SOCIETY, 2020)
The article reflects such issues as improving the creative approach and critical thinking skills of students as a result of the implementation of the project research method in the development of innovative ideas in the teaching of natural and humanitarian sciences at the University.